Cryopreserved leukapheresis enables scalable and distributed CAR-T manufacturing: a multi-platform comparative study - Menglin Ren; Xiaodie Wang; Jiangrui Chen; Yuanjian Xu; Yan Sun; Tao Liu; Qijun Qian; Zenghui Xu (Scientific Reports)
Abstract Cryopreserved leukapheresis is a scalable source for Chimeric antigen receptor T (CAR-T) manufacturing, yet it remains understudied (18.3% of 349 studies, 2010–2024). Current challenges include that cryopreserved leukapheresis lacks a standardized preparation process and has a low level of automation. Systematic validation of its clinical feasibility and platform compatibility is imperative. We carried out a series of optimizations, including the centrifugation procedure, the proportion of CS10, and the cryopreservation procedure. Eventually, a standardized cryopreserved leukapheresis process was established through a closed automated system. Subsequently, a systematic evaluation of the quality and functionality of cryopreserved leukapheresis was conducted. Results showed that cryopreserved leukapheresis achieved ≥ 90% post-thaw viability, with recovery and phenotypic profiles comparable to peripheral blood mononuclear cells (PBMCs). It exhibited a higher lymphocyte proportion than PBMCs (66.59% vs. 52.20%), correlating with enhanced CAR-T potential. Initial viability (91.0%) was lower than fresh samples (99.0%), but functional recovery post-electroporation and compatibility with both platforms were confirmed. In the non-viral CAR-T, lentiviral CAR-T, and Fast CAR-T platforms, cryopreserved leukapheresis and fresh leukapheresis were comparable in cell viability, expansion, cell phenotype, CAR + cell proportion, and cytotoxicity. This study comprehensively validated cryopreserved leukapheresis as a universal raw material for CAR-T manufacturing, preserving critical quality attributes (T-cell fitness, CAR functionality) without compromising consistency. Decoupling from fresh material logistics improves supply chain resilience. Protocol standardization and large-scale clinical validation remain critical next steps.